High-temperature self-lubricating wear-resistant nano-composite oxynitride coating as well as preparation method and application thereof
The AlCrVSiON nanocomposite oxynitride coating prepared by arc ion plating technology solves the contradiction between the self-lubricating performance and oxidation resistance of V-containing coatings at high temperatures, achieves the effect of low friction coefficient and low wear rate at high temperatures, and improves the service life of the tool.
Patent Information
- Application Number
- CN202510546909.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2025-07-22
AI Technical Summary
V-containing coatings form self-lubricating phases at high temperatures or frictions, which improve friction performance but reduce oxidation resistance. The rapid external diffusion of V elements leads to reduced mechanical properties and high wear rate, which limits its application in the field of high temperatures.
Arc ion plating technology is used to prepare high-temperature self-lubricated wear-resistant nanocomposite oxygen nitride coatings. By adjusting the partial pressure of oxygen elements, a nano-multilayer structure with alternating oxygen-rich layers and nitrogen-rich layers is formed. Combined with AlCrVSiON functional layer and CrN base layer, the oxidation resistance and wear resistance of the coating are improved.
It realizes a coating with both self-lubricating performance and wear resistance at high temperatures, reducing the friction coefficient and wear rate, and extending the service life of the tool.
Smart Images

Figure CN120350346A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical fields of tool coatings and surface coating technologies, and particularly relates to a high-temperature self-lubricating wear-resistant nano-composite oxynitride coating, a preparation method thereof, and an application thereof. Background Art
[0002] High-speed dry cutting is a green cutting technology developed based on the requirements of environmental protection and sustainable development strategies, and is the development trend of modern machining. When high-speed dry cutting difficult-to-machine materials, due to large cutting forces and high cutting temperatures, the temperature of the tool edge can reach over 1000 °C. At this high temperature, the tool material is prone to element diffusion, oxidation and other phenomena, resulting in the degradation of the tool material and tool failure. At the same time, the surface quality of the machined material also decreases. High-speed dry cutting has relatively strict requirements for tool materials, and ordinary tools can no longer meet the requirements. Excellent high-temperature performance is the key to high-speed cutting of difficult-to-machine materials. Coating the surface of cemented carbide tools by PVD technology to modify their surfaces is one of the most effective ways to solve this problem.
[0003] The AlCrSiN coating has a composite structure including amorphous and nanocrystalline phases, with high hardness and excellent oxidation resistance. However, at temperatures above 500 °C, the AlCrSiN coating exhibits a relatively large friction coefficient, causing a sharp rise in local temperature, accelerating tool wear, shortening its service life, and limiting the application of this coated tool in high-temperature fields. As is well known, elements such as V, Mo, and W generate Magnéli phases with easy shear planes during friction or oxidation at high temperatures, which can effectively reduce the friction coefficient of the coating. In particular, for the V element, the self-lubricating phase V2O5 generated by oxidation has a high ionization potential. The cations are completely separated and shielded by oxygen atoms. Most of the cations form bonds with oxygen ions, and the interaction force between cations is small, so strong covalent bonds or ionic bonds cannot be formed, and the shear force is small. In addition, this oxide has a relatively low melting point of 560 - 580 °C, and also plays a role in liquid lubrication when the temperature is higher than the melting point. Therefore, it has been widely used. Adding V element to the AlCrSiN coating to obtain a composite coating AlCrVSiN, the friction coefficient of this coating is as low as about 0.26 when grinding against an Al2O3 ball at 800 °C. Coated tools containing V can generate self-lubricating phases under high-temperature or friction conditions, improving the friction performance of the coating. However, the addition of the V element also reduces the oxidation resistance of the coating. The rapid outward diffusion of the V element causes a decrease in the mechanical properties of the coating at high temperatures and a relatively high wear rate, which is an urgent problem to be solved for the high-temperature application of current V-containing coatings.
[0004] Doping a certain content of oxygen element in the nitride coating results in better high-temperature friction performance than that of the nitride coating. People use PVD technology to prepare the AlCrON coating of nitrogen oxides, and the high-temperature friction coefficient and wear rate are significantly reduced. By rotating the substrate material in front of the arc target, the prepared nitrogen oxide coating has a self-assembled nano-multilayer structure, with oxygen-rich layers and nitrogen-rich layers alternating. The nano-multilayer interface also effectively prevents the rapid diffusion of V element and improves the oxidation resistance of the coating. However, there is no report on the AlCrVSiON coating at present.
[0005] In view of the above defects, the inventors of the present invention have finally obtained the present invention through long-term research and practice. Summary of the Invention
[0006] The object of the present invention is to solve the problem that the V-containing coating can generate a self-lubricating phase under the action of high temperature or friction, improving the friction performance of the coating. However, the addition of V element also reduces the oxidation resistance of the coating, and the rapid outward diffusion of V element causes the mechanical properties of the coating to decline at high temperature and the wear rate to be relatively high. The present invention provides a high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating, a preparation method thereof, and an application thereof.
[0007] To achieve the above object, the present invention discloses a high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating. The coating has a nano-composite structure of amorphous coating wrapping nanocrystals and is a multi-layer structure with oxygen-rich layers and nitrogen-rich layers alternating. The atomic percentage content of each element in the coating is as follows: Al 19.2 - 22.7 at.%, Cr 4.0 - 4.7 at.%, V 9.3 - 13.1 at.%, Si 3.0 - 4.1 at.%, O 15.0 - 48.4 at.%, N 15.7 - 40.4 at.%.
[0008] The coating includes an AlCrVSiON functional layer, a CrN underlayer, and a Cr ion implantation layer from top to bottom.
[0009] The present invention also discloses a preparation method of the above high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating, including the following steps:
[0010] S1, clamping the substrate material after grinding, polishing, and ultrasonic cleaning on the sample turntable in the PVD vacuum chamber, pre-pumping the background vacuum to 3 - 5×10 -3 Pa, and setting the temperature to 300 - 500 °C;
[0011] S2, opening the Ar gas flow valve, and adjusting the air pressure and bias voltage in the vacuum chamber to perform glow cleaning on the substrate for 10 - 30 min;
[0012] S3, adjusting the air pressure and bias voltage in the vacuum chamber, opening the Cr arc target, and performing etching pretreatment on the substrate to activate the surface of the substrate to improve the film-substrate bonding strength;
[0013] S4. Close the Ar gas, introduce N2 gas, adjust the air pressure and bias voltage, turn on the Cr arc target, and deposit the CrN transition layer by arc ion plating technology;
[0014] S5. Close the arc Cr target, introduce the mixed gas of N2 and O2, adjust the total air pressure, oxygen partial pressure and bias voltage, turn on the AlCrVSi arc target, and adjust the arc target current to deposit the nitrogen oxide coating.
[0015] In the step S1, the substrate material is single crystal Si, cemented carbide, stainless steel or polycrystalline alumina material.
[0016] In the step S2, the air pressure is 0.5 - 1.0 Pa, and the bias voltage is -800 - -1200 V.
[0017] In the step S3, the air pressure is 0.5 - 1.0 Pa, the bias voltage is -500 - -1000 V, the etching time is 5 - 10 min, and the current of the Cr target material is 60 - 150 A.
[0018] In the step S4, the flow rate of the introduced N2 gas is 100 - 300 sccm, the air pressure is 0.5 - 1.0 Pa, the bias voltage is -50 - -150 V, the current of the Cr target material is 60 - 150 A, and the deposition time is 5 - 10 min.
[0019] In the step S5, the total air pressure of the mixed gas is 2 - 4 Pa, the oxygen partial pressure accounts for 1 - 10% of the mixed air pressure, the bias voltage is -50 - -150 V, the target current of the pulsed arc target is 50 - 100 A, and the deposition time is 1 - 3 h.
[0020] The present invention also discloses the application of the above high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating in high-speed dry cutting tools.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0022] 1. The present invention provides a high-temperature self-lubricating and wear-resistant nitrogen oxide coating and its deposition method. By using arc ion plating technology and adjusting the partial pressure of oxygen element, the AlCrVSiON coating with different oxygen contents is deposited. The coating has a nano-composite structure, and at the same time, due to the rotation of the sample in front of the arc target, a nano-multilayer structure with alternating oxygen-rich layers and nitrogen-rich layers is formed. The coating has high-temperature self-lubrication and high-temperature stability at the same time, solving the problems of easy oxidation and high wear rate of the V-containing coating at high temperature;
[0023] 2. The AlCrVSiON nitrogen oxide coating of the present invention can obtain nano-composite multi-layer coatings with different oxygen contents by adjusting the partial pressure of oxygen in the mixed gas to meet different processing objects and cutting conditions. Description of the Drawings
[0024] Figure 1 Schematic diagram of the multi-layer structure of the AlCrVSiON nitride coating of the present invention;
[0025] Figure 2 XRD patterns of the coatings of Example 1, Example 2 and the comparative example of the present invention;
[0026] Figure 3 Surface and cross-sectional morphology diagrams of the coatings of Example 1 (b, e), Example 2 (c, f) and the comparative example (a, d) of the present invention;
[0027] Figure 4 Hardness diagrams of Example 1, Example 2 and the comparative example of the present invention;
[0028] Figure 5 Comparison diagrams of wear rates at different temperatures of Example 1, Example 2 and the comparative example of the present invention;
[0029] Figure 6 Results diagrams of surface and cross-section characterization analysis and adhesion metallographic test of Example 2 and Example 3 of the present invention using a scanning electron microscope and a scratch tester. Detailed Description of the Invention
[0030] The above and other technical features and advantages of the present invention will be described in more detail below with reference to the accompanying drawings.
[0031] Example 1
[0032] The nano-multi-layer structure of the self-lubricating wear-resistant nitride coating is as Figure 1 shown. The arc target used in this example is an AlCrVSi alloy target with a V content of 30 at.%, and the substrate material used is cemented carbide (WC-Co), and its composition is: WC - 8 wt.%, Co - 4 wt.%, and TiC - 88 wt.%.
[0033] The specific preparation method includes the following steps:
[0034] (1) Substrate pretreatment: The substrate after rough grinding, fine grinding and polishing is ultrasonically cleaned with acetone and absolute ethanol for 15 minutes respectively, dried with compressed nitrogen, and then clamped on the sample turntable of the PVD vacuum chamber so that the height position of the substrate material is directly opposite to the center of the arc target AlCrVSi;
[0035] (2) Prerelease the background vacuum to 5×10 -3Below Pa, turn on the heater and heat up to 450 °C. Start the sample turntable to rotate at a speed of 3 r / min. Open the argon valve, adjust the chamber pressure to 2 Pa, set the temperature to 400 °C, set the bias voltage to -1000 V, and perform glow cleaning on the sample substrate for 30 min; adjust the gas pressure to 0.5 Pa, adjust the substrate bias voltage to -800 V, turn on the Cr arc target, set the current to 100 A, perform Cr ion etching pretreatment on the substrate, set the etching time to 2 min, adjust the bias voltage to -600 V, and continue etching for 3 min.
[0036] (3) Close the argon gas valve, open the nitrogen valve, control the total chamber pressure to 0.5 Pa, set the bias voltage to -100 V, and the Cr target current to 100 A, and start depositing the CrN transition layer for 5 min;
[0037] (4) Turn off the Cr target power supply, introduce a mixed gas of N2 and O2, set the total gas pressure to 3.0 Pa, the O2 partial pressure accounts for 2% of the total gas pressure of the mixed gas, turn on the arc AlCrVSi target, set the pulsed arc target current to 60 A, set the bias voltage to -100 V, and deposit for 1.5 h;
[0038] (5) After the deposition is completed, turn off the arc target power supply and the bias voltage power supply. Wait for the temperature of the vacuum chamber to drop to room temperature, open the vacuum chamber and take out the sample to complete the coating.
[0039] In this embodiment, the atomic percentage content of each element in the prepared high-temperature self-lubricating and wear-resistant aluminum chromium vanadium silicon oxide nitride AlCrVSiON coating is: Al 22.7 at.%, Cr 4.7 at.%, V 13.1 at.%, Si 3.3 at.%, O 15.0 at.%, N 40.4 at.%.
[0040] Example 2
[0041] The difference between this embodiment and Example 1 is that in step (4), the O2 partial pressure accounts for 7% of the total gas pressure of the mixed gas, and other process steps are the same as those in Example 1. In this embodiment, the atomic percentage content of each element in the prepared high-temperature self-lubricating and wear-resistant aluminum chromium vanadium silicon oxide nitride AlCrVSiON coating is: Al 19.6 at.%, Cr 4.0 at.%, V 9.3 at.%, Si 3.0 at.%, O 48.4 at.%, N 15.7 at.%.
[0042] Example 3
[0043] The difference between this example and Example 2 is that: in step (1), the arc target used is an AlCrVSi alloy target with a V content of 10 at.%, and the other process steps are the same as those in Example 2. In this example, the atomic percentage contents of the elements in the prepared high-temperature self-lubricating and wear-resistant aluminum chromium vanadium silicon oxynitride (AlCrVSiON) coating are: Al 17.6 at.%, Cr 10.3 at.%, V 3.1 at.%, Si 2.8 at.%, O 54.9 at.%, N 11.3 at.%.
[0044] Comparative example
[0045] The difference between this example and Example 1 is that: in step (4), only N2 is introduced, and the other process steps are the same as those in Example 1. In this example, the atomic percentage contents of the elements in the prepared nitride coating AlCrVSiN are: Al 23.7 at.%, Cr 5.3 at.%, V 14.7 at.%, Si 4.2 at.%, N 15.7 at.%.
[0046] The phase structures of the coatings of Example 1, Example 2, and the comparative example were analyzed using an X-ray diffractometer (Bruker D8 ADVANCE, Cu K α ray source), and the XRD patterns are as Figure 2 shown. All the coatings exhibit a face-centered cubic (CrN) structure. Compared with the peak positions of the nitride in the comparative example (AlCrVSiN), the peak positions of the O-containing coatings shift towards higher angles. This is because the O element with a smaller atomic radius replaces some of the N elements with a larger atomic radius. According to Bragg's equation, the decrease in the d value leads to an increase in the angle. As the O content increases, the peak position shift of the coating becomes more obvious.
[0047] The surface and cross-sectional morphologies of the coatings of Example 1, Example 2, and the comparative example were observed and analyzed using a scanning electron microscope (FEI Nova Nano SEM 430), and their morphology diagrams are as Figure 3 shown. Large particles, which are characteristic defects of arc ion plating, exist on the surfaces of all three coatings, and the particles in Example 1 are smaller and the surface is relatively flat. The cross-sectional morphologies of all the coatings exhibit a typical columnar crystal structure, and the structure of Example 1 is dense.
[0048] The hardness tests of the coatings of Example 1, Example 2, and the comparative example were respectively carried out using a nanoindentation instrument (CSM, NHT 2 ), and the test results are as Figure 4As shown. The hardness of the comparative example (AlCrVSiN) coating is 29.0 GPa. After introducing oxygen, a nano-multilayer structure with alternating oxygen-rich layers and nitrogen-rich layers is formed, and the hardness of the coating increases. The hardness value of Example 1 is as high as 30.7 GPa. However, too much oxygen content causes the hardness of the coating to decrease. The hardness of the coating in Example 2 is only 25.3 GPa.
[0049] The friction performance tests of the coatings of Example 1, Example 2 and the comparative example were carried out at different temperatures using a ball-disk high-temperature friction and wear tester (CSM, THT1000). The counterbody is an alumina ball (Al2O3, ), the normal load is 5 N, the friction radius is 2 mm, and the linear velocity is 0.1 m / s. After the friction experiment, a laser confocal scanning microscope of model LEXT OLS4100 was used to measure and characterize the surface of the coating wear scar to calculate the wear rate of the coating. The wear rates of the above three coatings at room temperature (RT) and high temperature (800 °C) are as Figure 5 shown. Compared with the nitride coating AlCrVSiN (comparative example), the oxynitride coating has a lower wear rate under both RT and high temperature conditions. It shows that the oxynitride has better wear resistance than the nitride and can effectively improve the service life of the tool.
[0050] For Example 2 and Example 3, a scanning electron microscope (FEI Nova Nano SEM 430) and a scratch tester (Anton Paar, RST 3 ) were used for surface and cross-section characterization analysis, and a bonding force metallographic test was carried out. The test results are as Figure 6 shown. Through the surface-cross-section comparative analysis of Example 2 and Example 3, it is found that Example 2 with a higher V content exhibits a denser coating microstructure. The scratch test results show that the increase in V content can significantly improve the toughness of the coating, thereby improving the bonding performance between the coating and the substrate. This result shows that the V element plays an important role in refining the columnar crystal structure of the coating and improving the toughness of the coating, and can effectively extend the service life of the coating under complex working conditions such as impact.
[0051] The above are only the preferred embodiments of the present invention, which are illustrative rather than restrictive to the present invention. Those skilled in the art understand that many changes, modifications, and even equivalents can be made within the spirit and scope defined by the claims of the present invention, but all will fall within the protection scope of the present invention.
Claims
1. A high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating, characterized in that, The coating is a nanocomposite structure with an amorphous coating wrapping nanocrystals, and is a multi-layer structure with alternating oxygen-rich layers and nitrogen-rich layers. The atomic percentage content of each element in the coating is as follows: Al 19.2 - 22.7 at.%, Cr 4.0 - 4.7 at.%, V 9.3 - 13.1 at.%, Si 3.0 - 4.1 at.%, O 15.0 - 48.4 at.%, N 15.7 - 40.4 at.%.
2. The high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating according to claim 1, wherein The coating includes an AlCrVSiON functional layer, a CrN underlayer, and a Cr ion implantation layer from top to bottom respectively.
3. A method for preparing a high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating as described in claim 1 or 2, characterized in that, It includes the following steps: S1. The substrate material after grinding, polishing and ultrasonic cleaning is clamped on the sample turntable in the PVD vacuum chamber, and the background vacuum is pre-pumped to 3-5×10 -3 Pa, and the temperature is set to 300-500 °C; S2. Open the Ar gas flow valve, and adjust the air pressure and bias voltage of the vacuum chamber to perform glow cleaning on the substrate for 10 - 30 min. S3. Adjust the air pressure and bias voltage of the vacuum chamber, open the Cr arc target, and perform etching pretreatment on the substrate to activate the surface of the substrate to improve the film-substrate bonding strength. S4. Close the Ar gas, introduce N2 gas, adjust the air pressure and bias voltage, open the Cr arc target, and deposit a CrN transition layer by arc ion plating technology. S5. Close the Cr arc target, introduce a mixed gas of N2 and O2, adjust the total air pressure, oxygen partial pressure and bias voltage, open the AlCrVSi arc target, and adjust the arc target current to deposit a nitrogen oxide coating.
4. The preparation method of a high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating according to claim 3, characterized in that In the step S1, the substrate material is single crystal Si, cemented carbide, stainless steel or polycrystalline alumina material.
5. The preparation method of a high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating according to claim 3, characterized in that, In the step S2, the air pressure is 0.5 - 1.0 Pa, and the bias voltage is -800 - -1200 V.
6. The preparation method of a high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating as described in claim 3, characterized in that, In the step S3, the air pressure is 0.5 - 1.0 Pa, the bias voltage is -500 - -1000 V, the etching time is 5 - 10 min, and the current of the Cr target is 60 - 150 A.
7. The preparation method of a high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating as described in claim 3, characterized in that, In the step S4, the flow rate of the introduced N2 gas is 100 - 300 sccm, the air pressure is 0.5 - 1.0 Pa, the bias voltage is -50 - -150 V, the current of the Cr target is 60 - 150 A, and the deposition time is 5 - 10 min.
8. The preparation method of a high-temperature self-lubricating and wear-resistant nano-composite oxynitride coating according to claim 3, characterized in that, In the step S5, the total air pressure of the mixed gas is 2 - 4 Pa, the oxygen partial pressure accounts for 1 - 10% of the mixed air pressure, the bias voltage is -50 - -150 V, the target current of the pulsed arc target is 50 - 100 A, and the deposition time is 1 - 3 h.
9. Application of a high-temperature self-lubricating and wear-resistant nanocomposite oxynitride coating as described in claim 1 or 2 in a high-speed dry cutting tool.
Citation Information
Cited By
Cutting tool deposited with multiple nano-composite coatings and preparation method of cutting tool
CN122105326A